An enhanced quantum key distribution protocol for security authentication. (19th May 2019) - Kumar, Ankit; Dadheech, Pankaj; Singh, Vijander; Raja, Linesh; Poonia, Ramesh C.
Abstract: Quantum Cryptography is revolutionary discovery in the field of network security. Quantum cryptography promises to provide sophisticated functionality for security issues but it also leads to unbelievable increment in computational parallelism which is helpful for potential cryptanalytic attacks. Some of the associated properties of Quantum Key Distribution protocol that provide security that is deficient for the shared key to be transmitted securely. The identity verification process attempts to maximize success in interpreting the EPR protocol for distribution of Quantum.